Virus neutralisation by intracellular antibodies. (June 2022) - Bottermann, Maria; Caddy, Sarah L.
Abstract: For decades antibodies were largely thought to provide protection in extracellular spaces alone, mediating their effector functions by mechanisms such as entry-blocking, complement activation and phagocyte recruitment. However, a wealth of research has shown that antibodies are also capable of neutralising numerous viruses inside cells. Efficacy has now been demonstrated at virtually all intracellular stages of the viral life cycle. Antibodies can neutralise viruses in endosomes by blocking uncoating, fusion mechanisms, or new particle egress. Neutralisation can also occur in the cytosol via recruitment of the intracellular antibody receptor TRIM21. In addition to these direct neutralisation effects, recent research has shown that antibodies can mediate virus control indirectly by promoting MHC class I presentation and thereby increasing the CD8 T cell response. This provides valuable new insight into how non-neutralising antibodies can mediate potent protection in vivo. Overall, the importance of understanding the mechanisms of intracellular neutralisation by antibodies is highlighted by the ongoing need to develop new methods to control viruses. Using or inducing antibodies to block virus replication inside cells is now an innovative approach used by several vaccination and therapeutic strategies.